2021
DOI: 10.33137/cpoj.v4i1.36252
|View full text |Cite
|
Sign up to set email alerts
|

The Hybrid Subischial Socket for Persons With Transfemoral Amputation: Gait Parameters and Clinical Assessment of a Case Series

Abstract: BACKGROUND: The subischial socket interface design is a promising new shape of socket for persons with transfemoral amputation. Typically, the proximal trim line is located distal to the ischial tuberosity, improving comfort in prosthetic users without interfering with gait parameters compared to Ischial Containment Socket (ICS). No studies have investigated the performances of a subischial sockets with suction suspension system. A new subischial socket (Hybrid Subischial Socket - HySS) combined with a hypobar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In a previous study, 10 it has been shown that the use of this socket can improve hip range-of-motion, walking speed and distance, Timed Up and Go Test time, stride length, double support duration, the peak value of hip extension during stance, and the satisfaction with the prosthesis.…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, 10 it has been shown that the use of this socket can improve hip range-of-motion, walking speed and distance, Timed Up and Go Test time, stride length, double support duration, the peak value of hip extension during stance, and the satisfaction with the prosthesis.…”
Section: Introductionmentioning
confidence: 93%